Patients with dysphagia: How to supply nutrition through non-tube feeding - Shen, Zhean; Hou, Yingze; Huerman, Ayideng; Ma, Aiqin (Frontiers in Nutrition, 2022)
Objecetive: Dysphagia has become one of the important factors that cause malnutrition in the whole age group. At present, tube feeding is still the mainstream means to solve the problem of dysphagia. However, tube feeding has physical and mental harm to people, and the ways of non-tube feeding are relatively diversified. The significance of the thickening mechanism described in some articles to solve the problem of dysphagia is not clear. Design: Problem-based comprehensive review. Setting and Participants: All patients with dysphagia worldwide, including oropharyngeal dysphagia (OD) and non-oropharyngeal dysphagia. Method: We searched the literature in Pubmed, Web of Science and Cochrane Library and initially browsed the titles and abstracts. We reviewed the full text of the articles that met our topic, and the language of the article was limited to English. Results: We found that food thickening to a certain degree (350-1750 cP) can reduce the complications of choking, aspiration, reflux, and other complications in patients with dysphagia, and reduce the social disorder, anxiety, and other psychological problems caused by catheterization and surgery. Significantly, food science engineers should invite clinicians to intervene in the development of specialty foods from different perspectives such as clinical pathophysiology and fluid mechanics. Conclusion and Implications: It is necessary to develop special foods for patients with dysphagia, which requires scientists from different disciplines to work together.